The slow violence of racism on Asian Americans during the COVID-19 pandemic - Wong-Padoongpatt, Gloria; Barrita, Aldo; King, Anthony; Strong, Michelle (Frontiers in Public Health, 2022)
Racism against people of Asian descent increased by over 300% after the COVID-19 pandemic outbreak in the United States, with one in five Asian Americans reporting direct experiences with overt discrimination. Large-scale efforts and resources initially, and quite understandably, prioritized investigating the physiological impact of the coronavirus, which has partially delayed research studies targeting the psychological effects of the pandemic. Currently, two studies tracked the unique relationships between psychosocial factors, such as experiencing everyday racism, and the self-reported wellbeing of Asian Americans in the United States and compared these associations with Latinx Americans. Study 1 (April 2020–April 2021) examined how Asian and Latinx Americans varied in their levels of wellbeing, fear of the coronavirus, internalized racism, and everyday experiences with racism. Study 2 (September 2021–April 2022) included the same variables with additional assessments for victimization distress. We used the CDC Museum COVID-19 Timeline to pair collected data from our studies with specific moments in the pandemic—from its known origins to springtime 2022. Results highlighted how slow and deleterious forms of racist violence could wear and tear at the wellbeing of targeted people of color. Overall, this research underscores the possible hidden harms associated with slow-moving forms of racism, as well as some of the unseen stressors experienced by people of color living in the United States.